2004
DOI: 10.1111/j.1365-2966.2004.07663.x
|View full text |Cite
|
Sign up to set email alerts
|

Wolf-Rayet stars in M33 - I. Optical spectroscopy using CFHT-MOS

Abstract: We have obtained spectroscopy of a large sample of Wolf–Rayet stars in M33 with the Canada–France–Hawaii Telescope Multi‐Object Spectrograph (CFHT‐MOS), including 26 WC stars, 15 WN stars and a WN/C star. In general, spectral types are merely refined, although the spectral type of X9 from Massey & Johnson is revised from WNL?+abs to WC4+abs, whilst their G1 and C21 candidates are not confirmed as Wolf–Rayet stars. We also re‐examine the metallicity gradient of M33 from H ii regions and identify the present sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 56 publications
(107 reference statements)
2
15
0
Order By: Relevance
“…Schild, Smith & Willis (1990) have studied the WC content of M33 revealing a correlation between line width (C iv λ5808 FWHM) and galactocentric distance ( r / R 25 ), supported by results of Canada–France–Hawaii Telescope (CFHT) spectroscopy in Abbott et al (2004). In Fig.…”
Section: The Wolf–rayet Population Of Ngc 7793mentioning
confidence: 79%
See 1 more Smart Citation
“…Schild, Smith & Willis (1990) have studied the WC content of M33 revealing a correlation between line width (C iv λ5808 FWHM) and galactocentric distance ( r / R 25 ), supported by results of Canada–France–Hawaii Telescope (CFHT) spectroscopy in Abbott et al (2004). In Fig.…”
Section: The Wolf–rayet Population Of Ngc 7793mentioning
confidence: 79%
“…8, we re‐produce Fig. 6 from Abbott et al (2004) together with unpublished M33 William Herschel Telescope (WHT)/Wide‐field Fibre Optic Spectrograph (WYFFOS) data taken in 1998 August, plus our own NGC 7793 observations. Indeed, there is a deficit of broad‐lined WC4–6 stars at low galactocentric distances.…”
Section: The Wolf–rayet Population Of Ngc 7793mentioning
confidence: 99%
“…In M33, the Neugent & Massey (2011) catalogue only contains one WNh star. However, Hamann, Gräfener & Liermann (2006) listed many WNh stars in the Milky Way, providing circumstantial evidence that they should also exist in larger numbers in M33; one star in the Neugent & Massey (2011) catalogue is labeled "H-rich" but not classified WNh; one of the classification sources (Abbott et al 2004) intentionally omitted the Smith, Shara & Moffat (1996) WNh criteria; and one WN7h star from another source (Drissen et al 2008) is simply reported as a WN7 in Neugent & Massey (2011). Therefore, in M33, WN and WNh stars seem to be mixed and cannot be reliably separated.…”
Section: Resultsmentioning
confidence: 99%
“…At subSolar metallicities, the LMC and SMC have been well sampled (Breysacher et al 1999;Massey et al 2003), as has M 33 (Massey & Johnson 1998;Abbott et al 2004). In contrast, M 31 is the only Local Group member with super-Solar metallicity, but its unfavourable inclination and large spatial extent makes surveying the complete WR population very challenging.…”
Section: Introductionmentioning
confidence: 99%